2015
DOI: 10.2527/jas.2014-8285
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between purebred and crossbred body weight traits in Limousin and Limousin–Angus populations

Abstract: The purpose of this study was to estimate correlations between purebred and F1 crossbred performance to verify the appropriateness of current models used in multibreed selection. Records on birth weight (WB) and weaning weight (WW) from purebred Limousins (LIM) and Limousin × Angus progeny (F1) were used to estimate genetic parameters using a multiple-trait (purebred and F1 weights were different traits) approach. For WB, there were 148,647 records for LIM and 17,981 for F1, and for WW, there were 81,585 recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
4
17
0
Order By: Relevance
“…Other works on multiple trait evaluations, carried out with data on beef (Cardoso & Tempelman, 2004;Toral et al, 2012;Lukaszewicz et al, 2015) and dairy (Heins et al, 2011;VanRaden et al, 2011) cattle, showed that variances and heritabilities are specific to each genetic group. Similar results were obtained in the present study, since the additive genetic variances and heritabilities of AFC and 305MY were higher in the 1/2HG groups than in the 5/8HG and 3/4HG groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works on multiple trait evaluations, carried out with data on beef (Cardoso & Tempelman, 2004;Toral et al, 2012;Lukaszewicz et al, 2015) and dairy (Heins et al, 2011;VanRaden et al, 2011) cattle, showed that variances and heritabilities are specific to each genetic group. Similar results were obtained in the present study, since the additive genetic variances and heritabilities of AFC and 305MY were higher in the 1/2HG groups than in the 5/8HG and 3/4HG groups (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has already been adopted in other studies (Vallée et al, 2013;Lukaszewicz et al, 2015) and allows detecting differences related to variances and covariances. However, these models tend to become more parameterized as the number of genetic groups increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the additive genetic correlation between PB and CB performance, ). Across species, estimates of are generally lower than one for many trait categories (Wei and van der Werf 1995;Lukaszewicz et al 2015;. When is lower than one, PB selection candidates that have the highest BV for PB performance may not have the highest BV for CB performance.…”
Section: Selecting For Cb Performancementioning
confidence: 99%
“…The aim of such breeding programs is usually to maximize crossbred (CB) performance, while selection decisions are made in the parental lines, usually based on measurements of purebred (PB) performance. As a result, the response to selection in CB performance depends partly on the genetic correlation between PB and CB performance ( ), which is generally lower than one across species and trait categories (Wei and van der Werf 1995;Besbes and Gibson 1999;Newman et al 2002;Lukaszewicz et al 2015;Mulder et al 2016;Duenk et al 2019b). Hence, is an important parameter in breeding programs of pig and poultry.…”
Section: Introductionmentioning
confidence: 99%